Analisa Pengaruh Perubahan Fed Fund Rate, Index Harga Saham Gabungan dan Indeks LQ45 Terhadap Nilai Tukar Dollar Amerika – Rupiah - Ricky Suanto; Yanuar Yanuar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The economy in Indonesia is experiencing a decline which can be seen from the decline in the Composite Stock Price Index in Indonesia. The decline in the value of the Composite Stock Price Index and Liquid 45 Index (LQ45) affected the rupiah exchange rate against US dollars that have passed the psychological level limit of Rp. 15,000 per 1 USD. The weakening of the rupiah and the index value of the stock was triggered by an increase in interest rates set by the Federal which increase Fed Fund Rate to 2.25% in September 2018.This study aims to explain whether it is true that the announcement of changes in the central bank's fed funds rate in the United States can be related and influence the Stock Price Index and Exchange Rates in other countries, especially in Indonesia.After collecting and processing data with Path Analysis, the results show that the impact in average of the fed fund rate to the average return LQ45 index has the strongest effect compared to other variables, then the strongest effect value is produced by the effect of average return Composite Stock Price Index to the average return of the US Dollar - Rupiah which is negative 0.76. After going through the mediation process, the indirect effect that occurs between the average fed fund rate on the average return of the US Dollar – Rupiah is positive 0.451, which significantly stagnant and changes the direction of the effect compared to its direct effect of negative 0.46.